SOCRATES’ METHOD OF ‘NOT WRITING’ - Dushyant Kumar (Fedro, 2024)
In this paper, I intend to propound that Socrates’ choice of abstaining himself from writing not only leads to the “Socratic Problem” but also renders him vulnerable to misappropriations; a vulnerability he attributes to writing while substantiating his downright dismissal of it. The paper has been divided into three sections. In section one; effort is to contemplate “The Socratic Problem” which has been baffling scholars across centuries. Whether, for example, in Plato’s works, is it Plato’s or the historical Socrates’ views? Absence of Socrates’ own work has put his historical existence in a blurry picture and his character under shadows of doubts. In section two, there is an attempt to outline the debate between Phonocentrism and Oral tradition. Socrates is seen projecting phonocentric viewpoints in Plato’s Phaedrus, when he censures writing by invoking an Egyptian myth. In the last section, I have put forth a surmise that Plato’s Socrates must be an apotheosized and misappropriated version of the historical Socrates. And I question, if it can be taken as an insinuation that we need to consider possibility of misappropriation every time we read history without historicity.